(untitled) (Journal of Medical & Health Sciences Review, 2025)
This study reviews contemporary evidence comparing Open Pedicle Screw Fixation (OPSF) and Percutaneous Pedicle Screw Fixation (PPSF) for thoracolumbar fractures, focusing on radiological correction, operative parameters, clinical recovery, and complication profiles. Recent literature from 2019 to 2025 demonstrates that both techniques provide comparable outcomes in restoring vertebral height, correcting kyphosis, and achieving stable spinal alignment. However, PPSF consistently shows significant advantages, including reduced blood loss, shorter operative duration, minimal soft-tissue disruption, and faster postoperative recovery. MRI-based findings further confirm lower paraspinal muscle damage with PPSF, contributing to improved pain and functional outcomes such as VAS and ODI scores. Additionally, PPSF is associated with shorter hospital stays, lower infection rates, and higher screw-placement accuracy, particularly when navigation systems are used. Although OPSF remains effective for deformity correction, its greater invasiveness results in increased morbidity and delayed rehabilitation. Overall, existing evidence supports PPSF as a safe, minimally invasive, and clinically advantageous alternative to OPSF, though high-quality randomized controlled trials are still required to validate long-term radiological and functional equivalence..